2007
DOI: 10.1021/es061301x
|View full text |Cite
|
Sign up to set email alerts
|

Colloid Retention in Porous Media:  Mechanistic Confirmation of Wedging and Retention in Zones of Flow Stagnation

Abstract: A three-dimensional particle tracking model for colloid transport in porous media was developed that predicts colloid retention in porous media in the presence of an energy barrier via two mechanisms: (1) wedging of colloids within grain to grain contacts; (2) retention of colloids (without attachment) in flow stagnation zones. The model integrates forces experienced by colloids during transport in porous media, i.e., fluid drag, gravity, diffusion, and colloid-surface Derjaguin-Landau-Verwey-Overbeek interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
180
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(198 citation statements)
references
References 39 publications
17
180
1
Order By: Relevance
“…The issue we raise is not whether retention of secondary energy minimum associated colloids occurs, but rather, how it occurs. Our own simulations using a traditional force and torque balance for secondary energy minimum associated colloids show that colloids may be retained in zones of low fluid drag at the pore scale even without adhesive contact with the surface [Johnson et al, 2007]. In our model, retention without attachment occurred in rear stagnation zones, although these represent just one possible type of zone of low fluid drag.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…The issue we raise is not whether retention of secondary energy minimum associated colloids occurs, but rather, how it occurs. Our own simulations using a traditional force and torque balance for secondary energy minimum associated colloids show that colloids may be retained in zones of low fluid drag at the pore scale even without adhesive contact with the surface [Johnson et al, 2007]. In our model, retention without attachment occurred in rear stagnation zones, although these represent just one possible type of zone of low fluid drag.…”
mentioning
confidence: 72%
“…There are two important points here: (1) retention of secondary energy minimum associated colloids can be simulated in a system where colloid spinning and translation are allowed, and (2) spinning of the colloid in response to fluid shear does not necessarily lead to reentrainment. These two points, demonstrated by Johnson et al [2007] for secondary energy minimum associated colloids, contrast with the assumptions used by Torkzaban et al [2007Torkzaban et al [ , 2008 that (1) colloids may be immobilized by secondary energy minimum interaction; that is, secondary energy minimum interaction constitutes adhesive contact with the surface, and (2) the initiation of rolling can be equated to reentrainment.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Deposition of inert colloids is also significant in water disinfection, since microbes and inert colloids exhibit important similarities in saturated porous granular media, as stated by Johnson et al (2007) [1], who observed that hydrodynamic drag mitigates deposition and drives re-entrainment of both biological and non-biological colloids.…”
Section: Introductionmentioning
confidence: 92%
“…Regarding the implementation of the particle mechanics immersed in water, the model described does not include hydraulic retardation between particles, which would be required for high particle concentrations. The implementation of surface interaction, surface roughness and heterogeneity has not been taken into account, although it was argued to have significant effect on particle deposition [24,25].…”
Section: Limitations Of the Modelmentioning
confidence: 99%